The Single-phase AC Regulator on Base of Bidirectional IGBT Switches - Cimanis, Vladimirs; Hramcovs, Vladimirs; Rankis, Ivars (Electrical, Control and Communication Engineering, 2010)
In the work one of the methods for regulation of sinus shape AC voltage for middle-power loads with activeinductive character is observed. Such a regulator keeping output voltage of sinus shape must be fast-reacting and work in closed-loop system. It's shown, that for providing such features Buck and Boost pulse regulators can be applied. The only difference from DC pulse converters is that electronic switches in the system must be with bidirectional conductivity. For this reason an IGBT transistors can be applied with implemented in structure reverse diodes and if such two transistors are connected in series and with contrary conductivity then at activating both one of them will be in on-state. Realization of AC regulators with such switches is described in the work. Results of computer modeling also are given. Output voltage ripples are investigated on subject of their range and efficiency of filtering equipment on LC base. Such regulators can be applied for instance in electrical transport self supply systems.